ChemInform Abstract: Highly Enantioselective [4 + 2] Annulation via Organocatalytic Mannich‐Reductive Cyclization: One‐Pot Synthesis of Functionalized Piperidines. Issue 42 (1st October 2013) - Kumar, Indresh; Ramaraju, Panduga; Mir, Nisar A.; Singh, Deepika; Gupta, Vivek K.; Rajnikant, Rajnikant
Abstract The practicability of the described method is illustrated by gram‐scale application and through the synthesis of a functionalized (‐)‐anabasine derivative (IV*).